The Potentials of ChatGPT for Language Learning: Unpacking its Benefits and Limitations - Arif Nugroho; Nur Hidayanto Pancoro Setyo Putro; Kastam Syamsi (Register Journal, 2023)
The present study aims to unpack the potentials of ChatGPT for language learning based on students’ perspectives. Specifically, this study scrutinizes language learning needs that can be fulfilled by ChatGPT, potential benefits of ChatGPT, and limitations of ChatGPT for language education. Drawing on exploratory case study, this study involves 18 language students majoring in English education and linguistic studies from two public universities in Indonesia. The findings of semi-structured interviews and FGD reveal that ChatGPT shows great promise as a digital platform that can support personalize learning, stimulate authentic interactions, and boost student productivity. This study suggests that students can gain several advantages from ChatGPT to support their language learning, such as enhancing their writing skills (e.g., translation, paraphrasing, outlining, and receiving assistance with grammar and syntax), improving vocabulary acquisition, providing learning materials, and serving as conversation partner. However, students might encounter certain challenges when using ChatGPT for language learning, such as the risk of cheating and plagiarism, inaccurate responses, and ambiguous information which can lead to confusion and misunderstanding. This study offers fruitful insights for language education stakeholders (especially teachers and students) to enhance their digital competencies specifically related to the use of AI tools in language education.